Drosophila Importin-α2 is involved in synapse, axon and muscle development. - Timothy J Mosca; Thomas L Schwarz (PLoS ONE, 2010)
Nuclear import is required for communication between the cytoplasm and the nucleus and to enact lasting changes in gene transcription following stimuli. Binding to an Importin-α molecule in the cytoplasm is often required to mediate nuclear entry of a signaling protein. As multiple isoforms of Importin-α exist, some may be responsible for the entry of distinct cargoes rather than general nuclear import. Indeed, in neuronal systems, Importin-α isoforms can mediate very specific processes such as axonal tiling and communication of an injury signal. To study nuclear import during development, we examined the expression and function of Importin-α2 in Drosophila melanogaster. We found that Importin-α2 was expressed in the nervous system where it was required for normal active zone density at the NMJ and axonal commissure formation in the central nervous system. Other aspects of synaptic morphology at the NMJ and the localization of other synaptic markers appeared normal in importin-α2 mutants. Importin-α2 also functioned in development of the body wall musculature. Mutants in importin-α2 exhibited errors in muscle patterning and organization that could be alleviated by restoring muscle expression of Importin-α2. Thus, Importin-α2 is needed for some processes in the development of both the nervous system and the larval musculature.